Monitoring in the management of social programs - Espinoza-Beraún, Liz M (2020)
Objective. The research carried out had the objective of analyzing the follow-up process carried out by the accompaniment service for the families of the CUNA MÁS National Program, for an adequate quality management. Methods. It was a research with a quantitative approach, explanatory level, non-experimental design, transectional. The group of specialists from the Territorial Units of the Program was considered as a population, therefore, the sample consisted of 20 subjects. A questionnaire was used, previously validated by experts and reliable. The ethical considerations of the research were applied. Descriptive analysis was performed and hypotheses were tested. Results. The results show that the National Program Cuna Mas does not have a Monitoring System, but only a set of actions that are not operationalized in a real monitoring, showing serious limitations, since it lacks a conceptual theoretical framework and a Regulatory framework established and approved in a technical document that specifies the structure and function of the monitoring process, deadlines, managers, resources and instruments that facilitate the operation of monitoring actions. Conclusions. The Cuna Mas National Program does not have an adequate Monitoring System that negatively impacts the monitoring processes and actions to achieve the proposed results, affecting the quality of the management of the programs, which implies improvement actions.